2020
DOI: 10.1101/2020.07.23.217091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limits and Convergence properties of the Sequentially Markovian Coalescent

Abstract: Many methods based on the Sequentially Markovian Coalescent (SMC) have been and are being developed. These methods make use of genome sequence data to uncover population demographic history. More recently, new methods even allow the simultaneous estimation of the demographic history and other biological variables, extending the original theoretical frameworks. Those methods can be applied to many different species, under different model assumptions, in hopes of unlocking the population/species evolutionary his… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…For instance, genomewide variations of the mutation rate may have similar effects on the data than genomewide variations of N e , because high mutation rates and large population sizes both lead to increase the number of polymorphic sites in a region. Consistent with our results, Sellinger et al (2021) showed that applying SMC methods to genomic sequences that were simulated with local variations of the mutation rate leads to infer spurious population size declines. Actually, a direct consequence of N e heterogeneity is to increase the variance of coalescence times along the genome (see the Supplementary Materials for a proof of this statement under panmixia).…”
Section: Pros and Cons Of An Iicr Approachsupporting
confidence: 89%
“…For instance, genomewide variations of the mutation rate may have similar effects on the data than genomewide variations of N e , because high mutation rates and large population sizes both lead to increase the number of polymorphic sites in a region. Consistent with our results, Sellinger et al (2021) showed that applying SMC methods to genomic sequences that were simulated with local variations of the mutation rate leads to infer spurious population size declines. Actually, a direct consequence of N e heterogeneity is to increase the variance of coalescence times along the genome (see the Supplementary Materials for a proof of this statement under panmixia).…”
Section: Pros and Cons Of An Iicr Approachsupporting
confidence: 89%
“…Nevertheless, the obtained divergence time estimate concurs with previous mitochondrial estimates [22]. The Holocene population expansion of C. unifasciata inferred previously by phylogeographical methods [20] could not be resolved by PMSC with its limited power to infer very recent events [62].…”
Section: (A) Historical Demography Of Speciationsupporting
confidence: 85%
“…(2016) who found that high quality data (coverage >18x) are essential for proper inference. It has also been shown that high numbers of spurious SNPs (>10%) and unmasked repetitive sequences bias inference in several SMC methods (Sellinger et al., 2021). Many methods appear robust to the assembly quality (fragmentation) but their precision and accuracy differ across timescales (Patton et al., 2019)—often Ne for the most recent as well as ancient times is more difficult to infer.…”
Section: Biological and Methodological Limitations For Inferring The ...mentioning
confidence: 99%
“…An impressive number of new methods trying to improve resolution over recent timescales have been developed since the publication of the original PSMC study (Sellinger et al., 2021; Spence et al., 2018). In general, these methods improve the resolution by analysing genetic information from more individuals, from a few (Malaspinas et al., 2016; Schiffels & Durbin, 2014) to thousands (Speidel et al., 2019).…”
Section: Temporal Continuum Of Nementioning
confidence: 99%